Strength of lime-strengthened ashand-slag materials study - A. V. Zvyagintsev; A. А. Lunev; R. S. Katsarskiy; D. A. Shevchenko (Вестник СибАДИ, 2021)
Introduction. The article studies the strength of hardened ash-soil materials, with different ratios of pond ash, natural clay soil and lime in various proportions when adding a stabilizing additive “Sattelit”.Materials and methods. As part of the study, tests were carried out to determine the maximum density of dry soil and the optimal mixture of ash-soil materials (100% ash-and-slag mixture, 25% ash-and-slag and 75% loam and 50% ash-and-slag and 50% loam), and the subsequent determination of the ultimate strength for uniaxial compression at age seven, twenty-eight and ninety days. The samples were gaining strength in the normal hardening chamber. The samples are placed in a device for capillary water saturation of the samples.Results. As a result of the study, a regularity of the increase in the strength of the soil-ash mixtrues was revealed, depending on the amount of binder, the proportion of materials and the age of the mixture. It was also revealed that with an increase in the dosage of clay soil in the pond ash, the strength of the obtained soil-ash mixtrues sharply increases.Discussion and conclusion. The results of the studies carried out show the potential possibility of using zoological soil materials fortified with lime when installing an additional layer of the base of highways with capital or lightweight pavement on roads in the I-V road-climatic zone. However, additional research is required to determine the frost resistance and water resistance of zoological soil composites reinforced with lime.